2020
DOI: 10.1002/app.49966
|View full text |Cite
|
Sign up to set email alerts
|

Research on synthesis and thermal properties of poly(ethylene terephthalate) sulfonate group containing ionomer

Abstract: In order to solve the poor nucleation ability and slow crystallization rate of polyethylene terephthalate (PET), we propose a new strategy to prepare PET with self-nucleation ability based on the mechanism of mutual attraction of ions. In this study, a hydroxyl-terminated sulfonate monomer, sulfonated 1,4-butanediol (SBDO) without rigid structure was synthesized as nucleating agent functionalized PET third monomer, and then PET ionomers (PETi) were prepared through melt polycondensation with different contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Poly(ethylene terephthalate) ([η] = 0.68 g/dL) and UIO-66(Zr) (chemical structures illustrated in Figure 1 ) were prepared in the laboratory of the authors’ research group. PET was synthesized according to the method of our previous work [ 6 ]. UIO-66(Zr) was synthesized according to a method given in the the literature [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(ethylene terephthalate) ([η] = 0.68 g/dL) and UIO-66(Zr) (chemical structures illustrated in Figure 1 ) were prepared in the laboratory of the authors’ research group. PET was synthesized according to the method of our previous work [ 6 ]. UIO-66(Zr) was synthesized according to a method given in the the literature [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The slow crystallization rate seriously limits the application of the PET in engineering plastics fields [ 4 ], especially the manufacture of injection molded products. On the whole, such products with PET as the raw material require longer molding cycles and higher mold temperatures to be well prepared [ 5 , 6 ]. Accordingly, the improvement of the PET crystallization rate has always been a research hotspot in the application of PET to structural materials [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The melting enthalpy (ΔH m 100%) of 100% crystalline PET was reported in the literature as 140 J/g. 33 The tensile strength data of PET and PETEPOSS were acquired with the Intron universal tensile machine (USA). The sample size was 35 Â 2 mm dogbone-shaped sample.…”
Section: Characterizationsmentioning
confidence: 99%
“…The resulting sodium carboxylate chain end could evolve into the crystal nuclei, thereby enhancing its cold crystallization ability. Yue Yin et al [ 21 ] prepared PET ionomers (PETi) with different sulfonated 1, 4-butanediol (SBDO) contents through melt polycondensation. They found that due to the agglomeration of sulfonate ions in SBDO, SBDO became the nucleating agent for PETi crystallization, avoiding the deterioration of PET mechanical properties caused by the excessive addition of traditional nucleating agents.…”
Section: Introductionmentioning
confidence: 99%